Immune thrombocytopenic purpura with subsequent development of JAK2 V617F-positive essential thrombocythemia: Case Report - Marisabel Hurtado-Castillo; Brian Flaherty; Morris Jrada (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2021)
The sequential occurrence of Immune Thrombocytopenic Purpura (ITP) and Essential Thrombocythemia (ET) has been reported in the literature on a few occasions, as these are two hematologic disorders with distinct etiologies and patients usually have contrasting clinical presentations. Our case highlights the sequential occurrence of ITP, followed by Janus kinase 2 (JAK2) (V617F)-positive ET in a 64-year-old white woman, after four years of follow-up. The pathophysiology relating to these two conditions is incompletely understood, however, JAK2(V617F) mutation has been found in all the cases reported. Early identification of JAK2(V617F) mutation in a patient with a past medical history of ITP and presenting with thrombocytosis, may lead to a prompt diagnosis of ET and timely treatment initiation.